The Sociocultural Archaics of Bylinas in the Works of the Writer and Historian Lev Prozorov - Rakhno, Konstantin (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2024)
In the study of Northern Russian folk epics (bylinas), modern folklore studies persistently seek new paths and re-examine many established views. Historian and writer Lev Prozorov (1972–2020) left a scientific legacy that will continue to cause controversy for a long time and serve as a guide for many modern researchers of the bylina. Prozorov is characterized not only by a thorough, comprehensive knowledge of the material, but also, which is much less common, by an understanding of the Slavic ethnoreligious tradition, the culture of Kievan Rus and the peculiarities of the existence of Northern Russian epic tales. He outlined the contours of the historicism of the bylinas, approaching it through the study of their history, evolution, and transformation of the people’s worldview and ethnic religiosity. A number of his articles and the book “Times of Russian Bogatyrs” (2006) are devoted to the problem of studying bylinas. His work is based on primary sources, including annals and chronicles concerning the history of Rus and other Slavic countries, to the analysis of which Prozorov himself made a great contribution. While basing his work on nativist positions, he also used data from Celtic, Germanic, and Indo-Aryan mythology, legends, and tales, as comparative material. This allowed him to discover reflexes of Indo-European and Old Slavic images and motifs in bylinas. His analysis of the lexical features of the bylinas enabled him to reveal in them numerous echoes of an archaic, pre-Christian worldview. Prozorov also drew attention to traces of social-cultural archaism in bylinas such as the polytheism of their creators, descriptions of ancient potestary institutions and social structures, and medieval military customs.